1996
DOI: 10.1152/jappl.1996.81.3.1062
|View full text |Cite
|
Sign up to set email alerts
|

Minimal redistribution of pulmonary blood flow with exercise in racehorses

Abstract: We determined the spatial distribution of pulmonary blood flow at rest and during increasing levels of exercise (34, 59, and 90% of maximal oxygen consumption) in Thoroughbred racehorses (n = 4) using 15-microns fluorescent microspheres. After the horses were killed, the lungs were flushed free of blood, removed, air-dried at total lung capacity, and sliced into isogravitational planes, which were sampled in a systematic fashion for three-dimensional reconstruction. The fluorescence was measured for quantifica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
53
0
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(65 citation statements)
references
References 0 publications
11
53
0
1
Order By: Relevance
“…Using fluorescent microspheres , the pulmonary blood flow redistribution with exercise in Thoroughbred racehorses was previously found to be consistent with the location of exercise-induced pulmonary haemorrhagic (EIPH) lesions that are found in the caudodorsal lung regions (O'Callaghan et al 1987). The location, size and regional mismatching factors that were observed in R 1 demonstrated that most pulmonary perfusion redistribution occurs in the dorsal region of the lung in exercised healthy horses therefore confirming the findings of Bernard et al (1996). In a more recent experiment, this phenomenon was found to be associated with a change in fractal dimension, which suggests that mediators act on the pulmonary vasculature in exercising horses (Sinclair et al 2000).…”
Section: Discussionsupporting
confidence: 65%
“…Using fluorescent microspheres , the pulmonary blood flow redistribution with exercise in Thoroughbred racehorses was previously found to be consistent with the location of exercise-induced pulmonary haemorrhagic (EIPH) lesions that are found in the caudodorsal lung regions (O'Callaghan et al 1987). The location, size and regional mismatching factors that were observed in R 1 demonstrated that most pulmonary perfusion redistribution occurs in the dorsal region of the lung in exercised healthy horses therefore confirming the findings of Bernard et al (1996). In a more recent experiment, this phenomenon was found to be associated with a change in fractal dimension, which suggests that mediators act on the pulmonary vasculature in exercising horses (Sinclair et al 2000).…”
Section: Discussionsupporting
confidence: 65%
“…However, phasic changes in stroke volume, if these were to occur, would be most likely to covary with V T , which was accounted for in our model (via changes in intrathoracic pressure) rather than with the variability in heart rate occurring at the frequency of respiration (i.e., RSA). In addition, evidence suggests that preferential redistribution of flow, which could result in improved efficiency, does not occur with changes in cardiac output (4,18). Nonetheless, it is conceivable that phasic changes in stroke volume could account for the variance in ventilatory equivalents explained by RSA in our study.…”
Section: Discussionmentioning
confidence: 60%
“…Our selection of 15-m-diameter microspheres for the present study was influenced by previous reports examining the distribution of pulmonary blood flow in resting and exercising horses with this technique (2,6,21). However, in these reports, intrapulmonary arteriovenous shunting of 15-m-diameter microspheres was not examined.…”
Section: Discussionmentioning
confidence: 99%
“…However, in these reports, intrapulmonary arteriovenous shunting of 15-m-diameter microspheres was not examined. Although, in these experiments, cardiac (2,6,21) and other tissues may have been removed at necropsy, investigators did not report on the absence/presence of intravenously injected microspheres in the heart and/or other tissues.…”
Section: Discussionmentioning
confidence: 99%